2015
DOI: 10.1099/ijsem.0.000541
|View full text |Cite
|
Sign up to set email alerts
|

Aurantimicrobium minutum gen. nov., sp. nov., a novel ultramicrobacterium of the family Microbacteriaceae, isolated from river water

Abstract: Aurantimicrobium minutum gen. nov., sp. nov., a novel ultramicrobacterium of the family Microbacteriaceae, isolated from river water Graduate School of Biosphere Science, Hiroshima University, 1-4-4 Kagamiyama, Higashihiroshima, Hiroshima 739-8528, Japan A Gram-stain-positive, aerobic, non-motile, curved (selenoid), rod-shaped actinobacterium, designated KNC T , was isolated from the 0.2 mm-filtrate of river water in western Japan. Cells of strain KNC T were ultramicrosized (0.04-0.05 mm 3 ). The strain grew a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…were most abundant in the aquaponic system samples but were absent or at very low relative abundances in all RAS samples. Both of these organisms are common members of freshwater lake/river microbial communities (44, 45). On the basis of this limited data set, it seems likely that aquaponic systems select for more-natural aquatic communities than those of RAS, presumably because of the availability of the plant-derived or phytoplankton-derived nutrients that are common in lakes/rivers and that would be available in these systems, e.g., glycolate for Polynucleobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…were most abundant in the aquaponic system samples but were absent or at very low relative abundances in all RAS samples. Both of these organisms are common members of freshwater lake/river microbial communities (44, 45). On the basis of this limited data set, it seems likely that aquaponic systems select for more-natural aquatic communities than those of RAS, presumably because of the availability of the plant-derived or phytoplankton-derived nutrients that are common in lakes/rivers and that would be available in these systems, e.g., glycolate for Polynucleobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…Homology search against NCBI nr database of the sequences assigned to this genus suggested that Flavobacterium were potentially associated with assimilatory and dissimilatory of nitrogen compounds which are preceded by NO 3 - /NO 2 - transport into the cells. Alpinimonas isolated from river water and was likely to be important for dissolve organic matter removal (36). Norank_p_Saccharibacteria was a phylogenetically diverse group and played a role in the degradation of various organic compounds as well as sugar compounds under aerobic, nitrate reducing and anaerobic conditions (37).…”
Section: Discussionmentioning
confidence: 99%
“…A. minutum KNC T was originally isolated from a river in Japan (Nakai et al, 2015). The strain used in the present study was provided by the Biological Resource Center, NITE (NBRC) (Chiba, Japan).…”
Section: Strain and Growth Conditions For A Minutum Knc Tmentioning
confidence: 99%
“…We herein conducted a functional analysis of a rhodopsin and chemical analyses of pigments from the cosmopolitan freshwater Actinobacterium isolate, Aurantimicrobium minutum KNC T (Nakai et al, 2015), which belongs to the same family as R. lacicola. The A. minutum genome was reported in 2016 (Nakai et al, 2016); it contains a gene that encodes a putative light-driven, proton-pumping rhodopsin, Xanthorhodopsin (Balashov et al, 2005) -like rhodopsin (XLR), but lacks the blh gene.…”
mentioning
confidence: 99%